KESENJANGAN STRATEGI DAN KEAKTIFAN SISWA KELAS XI F 9 PADA PEMBELAJARAN PEMENTASAN DRAMA DI SMA NEGERI 1 MUARO JAMBI - Kenza Abelia Syaiputri; Fiya Andreadi; Helty; Liza Septa Wilyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the gap between learning strategies applied by the teacher and the level of student participation in drama performance learning in class XI F 9 at SMA Negeri 1 Muaro Jambi. The teacher had implemented well-planned and varied learning strategies, yet student active participation remained uneven. Using a qualitative descriptive approach, data were collected through structured observation, in-depth teacher interviews, and documentation. Results showed that the teacher met all indicators of learning planning, classroom management, and evaluation, including the implementation of Project-Based Learning (PBL). However, gaps were identified in student focus, low student confidence in question- and-answer sessions, uneven participation distribution, and the conventionality of instructional media. These findings confirm that effective planning does not automatically produce optimal student engagement. Integration of interactive digital media and direct appreciation strategies are recommended to bridge this gap.